Saami language policies in Saami archaeological research – Saemien gïelekonvensjovnh saemien arkeologijen dotkemisnie: Perspectives on research published in Finland – Perspektijvh dotkemi bïjre mah leah Soemesne bæjjoehtamme - Piha, Minerva (Fennoscandia Archaeologica, 2024)
In this article, the goal is to determine what the use and non-use of Saami archaeological terms ‒ for example, for different types of burials, dwellings, sacred sites, artefacts ‒ reveal about language policies in Saami archaeological research published in Finland from 1970 to 2019. The data of the research are Saami archaeological works published in scientific publication forums such as archaeological and multidisciplinary journals and publication series. The data contains 138 Saami archaeological works. From the data, I have collected the used Saami terms by the method of content analysis. The analysis of the data reveals that 65 different Saami terms is used in 63 publications. 39 of the terms are used only in one work, and only five terms are used in more than ten works. According to analysis, there are no formal policies or norms on how Saami terms should be used in archaeological research. Iktedimmie Daennie artihkelisnie goerehtem maam saemien termi pråvhkoe jïh ov-pråvhkoe arkeologijisnie gïelekonvensjovni bïjre soptseste. Saemien arkeologijen termh, v.g. ov-messie gaelmieh, årromesijjieh, bissiesijjieh jïh artefakth, daeverh mah arkeologijen dotkemisnie gååvnese. Manne daatam – dejtie saemien arkeologijen termide – arkeologijen jïh multidaajroen publikasjovnijste, goh aejkietjaalegijstie jïh dotkemeraajrojste, tjöönghkeme mah Soemesne bæjjoehtamme jaepeste 1970 jaapan 2019. Daatesne 138 saemien arkeologijen publikasjovnh, jïh manne sisvegen goerehtimmien vuekiem nuhtjeme gosse saemien termh tjöönghkeme jïh goerehtamme. Daatan goerehtimmie vuesehte 65 ov-messie saemien termh 63 publikasjovnine nuhtjesovveme. Golmeluhkieuktsie termh ajve akte publikasjovnesne, jïh ajve vïjhte termh jienebe goh luhkie publikasjovnine. Daate goerehtimmie vuesehte ij gååvnese naan byjjes gïele- jallh termenjoelkedassh guktie saemien termh arkeologijen dotkemisnie nuhtjedh.